Odonata of eastern Bangladesh with three new records for the country - M. Kawsar Khan (Journal of Threatened Taxa, 2018)
A study was conducted in the eastern region of Bangladesh to contribute to the knowledge of the country’s Odonata fauna.  A total of 75 species belonging to nine families was recorded during the study period from April 2014 to July 2016.  Two zygopteran species, Calicnemia imitans and Prodasineura autumnalis, and one anisopteran species, Megalogomphus smithii, are new records for the country.  The Megalogomphus genus is recorded for the first time from Bangladesh.